Strategy to Improve Accountability and Performance Management in Pamekasan Regency Government - Winoto, Suhartono (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
The level of accountability for the performance of the Pamekasan Regency Government in recent years has experienced a significant increase, so a strategy is needed so that the value of accountability continues to increase. The purpose of this study is to provide an overview of strategies for improving accountability and performance management in the government in Pamekasan Regency. The results of the study indicate that strategies for increasing accountability and performance management in the Pangandaran Regency Government include the Regional Apparatus Organization conducting a satisfaction survey on the community in each of its services periodically, the need to strengthen SOP (Standard Operating Procedures) in public services, increasing standard adjustments and review programs with community involvement (citizen charter), increasing the intensity level of coordination between regional apparatuses in order to improve public service innovation, providing and managing public complaints facilities, encouraging service innovation in each regional apparatus, and conducting periodic socialization of service evaluation policies.